Implementasi Sistem Pengendalian Intern Dalam Upaya Mewujudkan Optimalisasi Pendapatan Retribusi Daerah Pada Obyek Wisata Situ Bagendit Kabupaten Garut - Ungkari, Marti Dewi; Ningsih, Winda; Dany Merliyana , Reny (Institut Teknologi Garut, 2025)
Various efforts have been made by the Garut Regency Government to transform the city into a tourism destination that attracts visitors. Garut’s tourist destinations have the potential to become leading attractions in West Java, as they offer natural beauty and a refreshing climate. However, the management of Garut Regency’s tourist sites has not yet been optimal, which has affected the achievement of regional retribution revenue targets. Data obtained from the Garut Regency Tourism and Culture Office (Disparbud) indicate discrepancies between the projected regional revenue (PAD) and its realization. The urgency of this study lies in how to optimize regional retribution revenue from tourist sites in Garut Regency, given the current gap between budgeted targets and actual realization. The study aims to examine how internal control systems play a role in mediating the relationship between the utilization of human resources and technology in increasing PAD. This research is classified as quantitative, using primary data collected from respondents, including tourists, the Situ Bagendit Tourism Management Unit (UPT Situ Bagendit), and the Garut Regency Government, with a total of 100 samples. The method employed is Structural Equation Modeling (SEM) analysis using PLS. The findings reveal that the use of technology and human resources influences the Internal Control System, but does not directly affect Regional Original Revenue (PAD). In addition, the use of technology and human resources significantly impacts the implementation of the Internal Control System (SPI).